Possible relationship between antiphospholipid antibodies and embolic events in infective endocarditis. Issue 6 (5th January 2018) - Selton-Suty, Christine; Maigrat, Charles-Henry; Devignes, Jean; Goehringer, François; Erpelding, Marie-Line; Alla, François; Thivilier, Carine; Huttin, Olivier; Venner, Clément; Juilliere, Yves; Doco-Lecompte, Thanh; Lecompte, Thomas
Abstract : Objective: Antiphospholipid (aPL) antibodies may activate platelets and contribute to vegetation growth and embolisation in infective endocarditis (IE). We aimed to determine the value of aPL as predictors of embolic events (EE) in IE. Methods: We studied 186 patients with definite IE (Duke-Li criteria, all types of IE) from the Nanc-IE prospective registry (2007–2012) who all had a frozen blood sample and at least one imaging procedure to detect asymptomatic or confirm symptomatic EE. Anticardiolipin (aCL) and anti-β2 -glycoprotein I (β2 GPI) antibodies (IgG and IgM) were assessed after the end of patients' inclusion. The relationship between antibodies and the detection of EE after IE diagnosis were studied with Kaplan-Meier and Cox multivariate analyses. Results: At least one EE was detected in 118 (63%) patients (52 cerebral, 95 other locations) after IE diagnosis in 80 (time interval between IE and EE diagnosis: 5.9±11.3 days). At least one aPL antibody was found in 31 patients (17%). Detection of EE over time after IE diagnosis was more frequent among patients with anti-β2 GPI IgM (log-rank P=0.0036) and that of cerebral embolisms, among patients with aCL IgM and anti-β2 GPI IgM (log-rank P=0.002 and P<0.0001,  respectively). Factors predictive of EE were anti-β2 GPI IgM (HR=3.45 (1.47–8.08), P=0.0045), creatinine (2.74 (1.55–4.84), P=0.0005) and vegetation size (2.41 (1.41–4.12), P=0.0014). Those of cerebral embolism were aCL IgM (2.84 (1.22–6.62), P=0.016) and anti-β2 GPI IgM (4.77 (1.79–12.74), P=0.0018). Conclusion: The presence of aCL and anti-β2 GPI IgM was associated with EE, particularly cerebral ones, and could contribute to assess the embolic risk of IE.